"Some things are even worse than telling a child he is going to die": Pediatric oncology healthcare professionals perspectives on communicating with children about cancer and end of life. Issue 3 (26th December 2021) - Laronne, Anat; Granek, Leeat; Wiener, Lori; Feder‐Bubis, Paula; Golan, Hana
Abstract: Introduction: This study explored pediatric oncology healthcare professionals' (HCPs) perspectives on direct communication with children with advanced disease about their disease, palliative care, and end‐of‐life (EOL) communication. Methods: Forty‐six pediatric oncologists, nurses, psychosocial team members, and other HCPs from six hospital centers in Israel participated in semi‐structured interviews. The Grounded Theory method was used. Data were analyzed line‐by‐line with codes and categories developed inductively from participants' narratives. Results: HCPs viewed communication about disease progression and EOL as vital because children were often aware of their prognosis, because lack of communication could lead to emotional distress, and because communication is a prerequisite for shared decision‐making. HCPs identified several barriers for communication including HCP barriers (such as emotional strains, lack of training), parental barriers, guardianship law, and language and culture. HCPs also described strategies to promote EOL communication. Direct strategies include tailoring communication, allowing for silence, echoing children's questions, giving information gradually, and answering direct questions honestly. Indirect strategies included encouraging parents to talk to their children and teamwork with colleagues. Conclusions: Open communication with children who have cancer is essential. Nevertheless, multiple barriers persist. The rising accessibility of online information calls for urgent training of HCPs in communication so that children will not turn to unmediated and potentially misleading information online in the absence of HCP communication. Evidence‐based effective communication training modules and emotional support should be offered to HCPs. Knowledge about children's development, age‐appropriate communication, and cultural sensitivity should be included in this training.